Exploring the Drivers of Research Productivity: A Study of Motivation and Hygiene Factors Among Academics - Yener, Can (Journal of Policy Options, 2021)
The purpose of this study is to explore the impact of motivation and hygiene factors on the research performance of faculty members at a Turkish Foundation University, with a specific focus on the number of articles published in prominent academic indexes such as the Science Citation Index and Social Science Citation Index. Understanding how these factors influence academic productivity is crucial for enhancing the research output of universities and fostering a supportive academic environment. Motivation factors refer to elements that directly enhance job satisfaction and drive individuals to achieve higher levels of performance, such as recognition, achievement, career advancement, and the intrinsic enjoyment of research. On the other hand, hygiene factors include external conditions like salary, work environment, job security, and institutional policies that, if inadequate, may lead to dissatisfaction but do not necessarily motivate individuals to perform at higher levels. By examining the distinct roles of these factors, this study aims to uncover which aspects of the work environment and professional life have the most significant influence on academic performance, particularly in terms of research output. This insight can help university administrators and policymakers design strategies to enhance faculty motivation and improve overall research productivity. The study was conducted with a sample of 150 academics from the Turkish Foundation University, providing a diverse range of insights from faculty members across different disciplines. The focus on publications in the SCI and SSCI indexes ensures that the research performance being measured is of high academic and international standards. The results of this study could serve as a valuable resource for both academic institutions in Turkey and beyond, helping them better understand the drivers of academic success and implement policies that foster an environment conducive to research excellence. The study seeks to contribute to the broader discourse on academic productivity by identifying the key factors that influence the research output of university faculty members. By comparing the effects of motivation and hygiene factors, the study provides a nuanced perspective on how universities can optimize their resources and support systems to encourage greater research performance, leading to higher-quality academic contributions and enhanced institutional reputations. The study yielded several key results regarding the impact of hygiene and motivation factors on research performance among academics. First, it was found that the perception of academics toward the influence of hygiene factors—including salary, job security, company policies and administration, supervision, interpersonal relations, and working conditions—on their research performance is generally positive, with one notable exception: status. While most of these external factors were seen as contributing positively to research productivity, the perception of status did not align with this trend, indicating that academics do not perceive status as a significant driver of their research output. Second, the study revealed that academics had a consistently positive perception of the impact of motivators on their research performance. These motivators, which include opportunities for growth, the nature of the work itself, responsibility, achievement, advancement, and recognition, were all seen as influential in driving research productivity. This suggests that intrinsic factors, such as the personal fulfillment and professional development that come with academic work, are viewed by academics as strong motivators for achieving higher research performance. These findings highlight the importance of both extrinsic and intrinsic factors in shaping academic productivity, with a particular emphasis on how motivators can enhance research output. While hygiene factors such as salary and working conditions are important for maintaining a positive work environment, it is the motivators—like the sense of achievement and opportunities for growth—that appear to play a more crucial role in driving research performance among academics. This distinction can provide valuable insights for universities seeking to improve faculty research output by focusing on policies that enhance both the working environment and opportunities for professional development.